Evaluating The Quality Of The Educational Infrastructure From The Perspective Of Graduate Students - جنبلاط مادلين (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The educational infrastructure is the important factor for graduate students and faculty members today. As the availability of the educational infrastructure in universities significantly helps in the development of the scientific production of graduate students, and due to the importance of the topic, the study problem centered on the following question: What is the reality of the educational infrastructure in the college in question. The study also aimed at the following: To clarify the reality of existing libraries and the degree to which they meet the needs of postgraduate students, to indicate the level of available electronic services, in addition to revealing the reality of offices and classrooms, determining the reality of the available administrative services, in addition to explaining the reality of other support services. The descriptive analytical approach was used, and the data was studied and analyzed using version 25 of the SPSS program, and after analyzing the data, the study reached a set of results, the most important of which are the following: Postgraduate students’ dissatisfaction with the reality of the current educational infrastructure represented by the five axes (libraries, electronic services, Books and classrooms, administrative services, other services). The services of libraries and electronic services are among the most important services that must be developed as quickly as possible from the viewpoint of graduate students at the Faculty of Arts at Tishreen University.